Application-optimized FPGAs design using RTL-designed FPGAs architectures - Tomoaki Sato; Anyu Murakami; Sorawat Chivapreecha; Phichet Moungnoul (My University, 2025)
RTL-Designed Field-Programmable Gate Arrays (FPGAs) can describe FPGA functionality using Hardware Description Languages (HDLs), which means they can be easily customized to configure the FPGA. In conventional FPGAs, switches are used for routing control, making it impossible to design them using HDLs. This study leverages the customizable nature of RTL-Designed FPGAs to explore the optimal configuration of FPGAs for packet processing in computer networks. It demonstrates that a 4-input Look-Up Table (LUT) is superior to a 3-input LUT in terms of throughput and reveals that, as the number of LUT inputs increases, having 5 routing paths is more optimal than 4.
Keywords: Embedded Systems Design Techniques; Interconnection Networks and Systems; Real-Time Systems Scheduling